A Novel Antigenic Site Spanning Domains I and III of the Zika Virus Envelope Glycoprotein Is the Target of Strongly Neutralizing Human Monoclonal Antibodies - Graham, Stephen D. (J Virol, 2021)
Zika virus (ZIKV), a mosquito-transmitted flavivirus, caused a large epidemic in Latin America between 2015 and 2017. Effective ZIKV vaccines and treatments are urgently needed to prevent future epidemics and severe disease sequelae. People infected with ZIKV develop strongly neutralizing antibodies linked to viral clearance and durable protective immunity. To understand the mechanisms of protective immunity and to support the development of ZIKV vaccines, we characterize here a strongly neutralizing antibody, B11F, isolated from a patient who recovered from ZIKV. Our results indicate that B11F targets a complex epitope on the virus that spans domains I and III of the envelope glycoprotein. While previous studies point to quaternary epitopes centered on domain II of the ZIKV E glycoprotein as targets of strongly neutralizing and protective human antibodies, we uncover a new site spanning domains I and III as a target of strongly neutralizing human antibodies. IMPORTANCE People infected with Zika virus develop durable neutralizing antibodies that prevent repeat infections. In the current study, we characterize a ZIKV-neutralizing human monoclonal antibody isolated from a patient after recovery. Our studies establish a novel site on the viral envelope that is targeted by human neutralizing antibodies. Our results are relevant to understanding how antibodies block infection and to guiding the design and evaluation of candidate vaccines.